2019
DOI: 10.1002/jcp.28511
|View full text |Cite
|
Sign up to set email alerts
|

Microvesicles of osteoblasts modulate bone marrow mesenchymal stem cell‐induced apoptosis to curcumin in myeloid leukemia cells

Abstract: Microvesicles (MVs) derived from bone marrow niche components have an important role in genetic reprogramming and subsequent drugs induce apoptosis in leukemic cells. Here, we have found that undertreatment of curcumin or daunorubicin, the cross‐talk through MVs of KG‐1‐bone marrow mesenchymal stem cells (BMSCs), significantly downregulates the expression of the survival gene osteopontin (OPN), CXCL‐12, IL‐6 (interleukin‐6), STAT‐3, and VCAM‐1 (vascular cell adhesion molecule 1) in treated‐KG‐1 cells as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“…A recent study reported that BMSCs-EVs could enhance Imatin-induced apoptosis in human leukemia cells [7]. In this study, BMSCs-EVs could potentiate ALL cell apoptosis and repress proliferation, which verified the reported latent capacity of BMSCs-EVs to partially induce apoptosis of leukemia cells and to be applied in the supportive treatment of leukemia [27,28]. Similar to the previous studies, our results confirmed that MSCs-EVs had anti-proliferative and pro-apoptotic properties in leukemia cells despite the varied origin of EVs and techniques used [9,29,30].…”
Section: Effects Of Bmscs-evs On All Cellssupporting
confidence: 85%
“…A recent study reported that BMSCs-EVs could enhance Imatin-induced apoptosis in human leukemia cells [7]. In this study, BMSCs-EVs could potentiate ALL cell apoptosis and repress proliferation, which verified the reported latent capacity of BMSCs-EVs to partially induce apoptosis of leukemia cells and to be applied in the supportive treatment of leukemia [27,28]. Similar to the previous studies, our results confirmed that MSCs-EVs had anti-proliferative and pro-apoptotic properties in leukemia cells despite the varied origin of EVs and techniques used [9,29,30].…”
Section: Effects Of Bmscs-evs On All Cellssupporting
confidence: 85%
“…Osteoprotegerin (OPG) is secreted out of the cell by osteoblast and antagonizes the osteoclast development induced by RANKL ( 10 ). Mesenchymal stem cells in bone marrow proliferate and differentiate to form osteoblasts ( 13 ). Osteoblasts secrete various osteogenic active substances, regulate extracellular matrix maturation, and promote bone formation.…”
Section: Introductionmentioning
confidence: 99%